New Lower Cretaceous wasps (Insecta: Hymenoptera) of the Democratic People's Republic of Korea. (April 2023) - Ri, Song; So, Kwang Sik; Won, Chol Guk; Ri, Chol Jun
Abstract: Three new wasps of Hymenoptera are described from the Lower Cretaceous (Barremian–Aptian) Sinuiju Formation in Paektho-dong, Sinuiju City, North Phyongan Province, DPRK. They are: Angarosphex ryonsangiensis sp. nov. (Angarosphecidae), Pompilopterus sinuijuensis sp. nov. (Angarosphecidae), Paekthohelorus sinuijuensis gen. et sp. nov. (Heloridae). Besides them, Amplicella Kopylov from the Sinuiju Formation is also described: A. exquisitissima Kopylov et Zhang, 2015. These fossils confirm the proximity of the Sinuiju and Yixian faunas. Highlights: Three new wasps of Hymenoptera are described from the DPRK. These fossils highlight the diversity of the hymenopterans from the Sinuiju Biota. They expand our knowledge of the morphology of Angarosphecidae and Heloridae.